Equations of the heart and mind: a path analysis of psychological factors influencing mathematics performance - Nestor L. Gicaraya; Tedric Dave E. Senosa; Dolly Rose F. Temelo; Roberto G. Sagge, Jr.; Salvador P. Bacio, Jr.; Sybel Joy Farillon-Labis; Cheryl Lyn C. Delgado; Peter Ernie D. Paris (Institute of Advanced Engineering and Science, 2026)
Mathematics performance remains a significant concern in higher education, as learners’ affective and motivational factors critically shape their achievement outcomes. In this context, the present study explored how anxiety, attitude, motivation, and academic well-being influence students’ performance in mathematics using a quantitative descriptive-correlational design with path analysis. Using a validated researcher-made questionnaire, data were gathered from 369 undergraduate students. The instrument demonstrated sound reliability and validity. Statistical analyses comprising descriptive measures and structural equation modeling (SEM) were conducted to identify both direct and mediated relationships among variables. Findings showed that students generally experienced moderate levels of mathematics anxiety and favorable levels of motivation and academic well-being. Correlation results revealed that anxiety was negatively linked to all other factors, whereas attitude, motivation, and academic well-being were positively associated with mathematics performance. Path analyses further indicated that motivation and academic well-being directly enhanced performance, while anxiety negatively affected achievement indirectly by lowering students’ attitudes and motivation. The final model demonstrated an excellent fit, suggesting that emotional and motivational mechanisms play a vital role in determining mathematics success. These results underscore the need for educational strategies that help students manage anxiety and strengthen their motivation and well-being to support sustained academic achievement.